In vitro Assessment of the DNA Damage Response in Dental Mesenchymal Stromal Cells Following Low Dose X-ray Exposure - Belmans, Niels; Gilles, Liese; Welkenhuysen, Jonas; Vermeesen, Randy; Baselet, Bjorn; Salmon, Benjamin; Baatout, Sarah; Jacobs, Reinhilde; Lucas, Stéphane; Lambrichts, Ivo; Moreels, Marjan (Frontiers in Public Health, 2021)
Stem cells contained within the dental mesenchymal stromal cell (MSC) population are crucial for tissue homeostasis. Assuring their genomic stability is therefore essential. Exposure of stem cells to ionizing radiation (IR) is potentially detrimental for normal tissue homeostasis. Although it has been established that exposure to high doses of ionizing radiation (IR) has severe adverse effects on MSCs, knowledge about the impact of low doses of IR is lacking. Here we investigated the effect of low doses of X-irradiation with medical imaging beam settings (<0.1 Gray; 900 mGray per hour), in vitro, on pediatric dental mesenchymal stromal cells containing dental pulp stem cells from deciduous teeth, dental follicle progenitor cells and stem cells from the apical papilla. DNA double strand break (DSB) formation and repair kinetics were monitored by immunocytochemistry of γH2AX and 53BP1 as well as cell cycle progression by flow cytometry and cellular senescence by senescence-associated β-galactosidase assay and ELISA. Increased DNA DSB repair foci, after exposure to low doses of X-rays, were measured as early as 30 min post-irradiation. The number of DSBs returned to baseline levels 24 h after irradiation. Cell cycle analysis revealed marginal effects of IR on cell cycle progression, although a slight G2/M phase arrest was seen in dental pulp stromal cells from deciduous teeth 72 h after irradiation. Despite this cell cycle arrest, no radiation-induced senescence was observed. In conclusion, low X-ray IR doses (< 0.1 Gray; 900 mGray per hour), were able to induce significant increases in the number of DNA DSBs repair foci, but cell cycle progression seems to be minimally affected. This highlights the need for more detailed and extensive studies on the effects of exposure to low IR doses on different mesenchymal stromal cells.